Crowd Physics: Studies of Collaborative Opportunities in Spatiotemporal Networks of People - Horvitz, Eric; Krumm, John; Sadilek, Adam (Faculty Summit 2014, 2014)
Understanding & Shaping Collaborative Systems Studies of crowd physics for sensing & acting in world Design, optimization of collaborative substrate Rich area, multiple directions for enhancing collaboration Opportunities include new approaches to epidemiology, e.g., where reachability & efficiency are minimized